Recensiones - I. M. B.; S. A.; Martínez, Jaime; S. de Anitua; A. P.; S. M. (ECA: Estudios Centroamericanos, 1971)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 26, No. 271, 1971: 293-309.